A case of Miller Fisher syndrome with multiple cranial nerves enhancement on MRI - Petcharunpaisan, Sasitorn; Lerdlum, Sukalaya (Chulalongkorn Medical Journal, 2023)
Miller Fisher syndrome is a clinical variant of Guillain-Barre syndrome with classic triad of ophthalmoplegia, ataxia and areflexia which there were some reports of multiple cranial nerves enhancement on MRI. We report a case of 66-year-old male presenting with headache and numbness of hands and feet, then gradual developed bilateral diplopia, ptosis, decreased deep tendon reflex and impaired tandem gait. Post contrast MRI showed multiple cranial nerves enhancement. Miller Fisher syndrome was diagnosed based on clinical triad and electrophysiologic evidence of polyneuropathy involved axon and myelin. We suggested that thin slice section of the post contrast MRI is likely to be helpful for detection of these abnormalities.